2018
DOI: 10.3324/haematol.2018.198820
|View full text |Cite
|
Sign up to set email alerts
|

Long-term real-world results of ibrutinib therapy in patients with relapsed or refractory chronic lymphocytic leukemia: 30-month follow up of the Swedish compassionate use cohort

Abstract: Long-term real-world results of ibrutinib therapy in patients with relapsed or refractory chronic lymphocytic leukemia: 30-month follow up of the Swedish compassionate use cohort LETTERS TO THE EDITOR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 8 publications
10
45
2
Order By: Relevance
“…However, we found 39.0% of all patients had at least one grade ≥3 infection, which is higher than reported in the RESONATE study (24%), 4 but in line with the long‐term follow‐up Swedish real‐world study reporting 51% of the patients with a grade 3‐4 infection. 23 This illustrates the importance of real‐world studies, since the results likely reflect how older and more frail patients included in real‐world studies are at higher risk of infections. We further demonstrated that the rate of infections was highest during the first 6 months, similar to what has been reported in previous clinical trials 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, we found 39.0% of all patients had at least one grade ≥3 infection, which is higher than reported in the RESONATE study (24%), 4 but in line with the long‐term follow‐up Swedish real‐world study reporting 51% of the patients with a grade 3‐4 infection. 23 This illustrates the importance of real‐world studies, since the results likely reflect how older and more frail patients included in real‐world studies are at higher risk of infections. We further demonstrated that the rate of infections was highest during the first 6 months, similar to what has been reported in previous clinical trials 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have described dose reductions in approximately 15%–30% of ibrutinib‐treated patients [2–4, 18]. Across varied patient cohorts evaluating dose reductions, consistent findings of no significant differences in PFS or OS have been reported [3, 18–22]. Temporary interruptions in treatment appear more frequent, with estimates ranging from 35% of patients in clinical practice [4] to 65% of those treated on clinical trials [2].…”
Section: Discussionmentioning
confidence: 94%
“…Clinical trials and real-world data on ibrutinib treatment in frontline and relapse-refractory settings in CLL/SLL patients showed a favorable safety profile [4,13,[15][16][17]51,[53][54][55][56][57][58][59][60][61][62]. The prevailing ibrutinib-related adverse events included diarrhea (up to 60%), arthralgia (up to 40%), rash (up to 25%), infections mainly of the upper respiratory tract (up to 35%) and mild hematological toxicity occurred in up to 60% of patients.…”
Section: Ibrutinib Adverse Eventsmentioning
confidence: 99%
“…Although ibrutinib treatment was well tolerated, some unexpected adverse events, probably due to off-target activity, have also been reported and included mainly atrial fibrillation and hemorrhagic complications [4,13,[15][16][17]51,[53][54][55][56][57][58][59][60][61][62]. Atrial fibrillation occurs in approximately 6-16% patients, predominantly in the first 6 months of treatment and is mostly grade 1-2 [63,64].…”
Section: Ibrutinib Adverse Eventsmentioning
confidence: 99%